HUBUNGAN PERSEPSI SISWA DENGAN MOTIVASI BELAJAR DALAM PEMBELAJARAN MATEMATIKA SMA NEGERI PONTIANAK - Purnama, Bayu Chandra Eka; Nuraini, Clarisa (UNIVERSITAS TANJUNGPURA, 2025)
Perception is the process of assigning meaning to various stimuli received by the senses, then organizing them to form a structured and meaningful picture, and finally resulting in an understanding of a situation. Additionally, motivation to learn mathematics is also an important factor in achieving optimal learning outcomes. The purpose of this study is to identify the relationship between students' perceptions of mathematics learning and their motivation to learn mathematics using the quantitative method of Pearson correlation test. The data collection technique involves perception questionnaires to measure students' perceptions and motivation questionnaires to measure students' learning motivation. The population in this study consists of 10th-grade students 2024/2025. Using the simple random sampling technique, a sample of 33 students was obtained. It can be concluded from the research results and data that have been analyzed that the results of the correlation coefficient (r) are 0.803 and the coefficient of determination (R square) is 0.64. This indicates that there is a very strong relationship between students' perceptions of learning mathematics and their motivation to learn and the contribution of students' perceptions to students' learning motivation is 64%